2013
DOI: 10.1080/10810730.2012.688250
|View full text |Cite
|
Sign up to set email alerts
|

Communication Competence, Social Support, and Depression Among College Students: A Model of Facebook and Face-to-Face Support Network Influence

Abstract: This study examined the influence of the social networking site Facebook and face-to-face support networks on depression among (N = 361) college students. The authors used the Relational Health Communication Competence Model as a framework for examining the influence of communication competence on social support network satisfaction and depression. Moreover, they examined the influence of interpersonal and social integrative motives as exogenous variables. On the basis of previous work, the authors propose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 59 publications
6
143
0
2
Order By: Relevance
“…Relative to strong ties, weak ties can be more objective, provide novel information, and present less potential for role conflict (Wright & Miller, 2010). Several studies have shown that individuals who prefer weak-tie support are more inclined to participate in computer-mediated support groups or experience greater benefits from their participation (Wright & Rains, 2013;Wright et al, 2012). Other research indicates that factors such as anonymity (Tanis, 2008), similarity (Wright, 2002), and accessibility (Walther & Boyd, 2002) are additional reasons that individuals may choose computer-mediated resources for acquiring social support.…”
Section: Social Support and Computer-mediated Communicationmentioning
confidence: 99%
“…Relative to strong ties, weak ties can be more objective, provide novel information, and present less potential for role conflict (Wright & Miller, 2010). Several studies have shown that individuals who prefer weak-tie support are more inclined to participate in computer-mediated support groups or experience greater benefits from their participation (Wright & Rains, 2013;Wright et al, 2012). Other research indicates that factors such as anonymity (Tanis, 2008), similarity (Wright, 2002), and accessibility (Walther & Boyd, 2002) are additional reasons that individuals may choose computer-mediated resources for acquiring social support.…”
Section: Social Support and Computer-mediated Communicationmentioning
confidence: 99%
“…These capabilities give an individual ability to adapt to and behave appropriately in situations that require a sensitive response and certain expected behaviors within the situations (Eisenberg et al, 2006;Sebanc, 2003). Researchers have found associations between social competence in parenting, temperament, peer group influences, interpersonal interactions, and cognitive abilities (Lindsey & Colwell, 2013;Schlundt & McFall, 1985;Wright, Rosenberg, Egbert, Ploeger, Bernard, & King, 2013).…”
Section: Social Competence Empathy and Communication Skillsmentioning
confidence: 99%
“…This change may cause stress or even depression, lack of appetite and concentration problems (Thurber & Walton, 2012). Leaving home and being outside parental control and supervision is an unprecedented challenge (Mahmoud, Staten, Hall & Lennie, 2012;Moreno, Jelenchick, Koff & Eickhoff, 2012;Wright et al, 2012). According to current research studies, a higher degree of load can also be caused by social networks and the content of shared posts from friends (Chou & Edge, 2012;Jelenchick, Eickhoff, & Moreno, 2013).…”
Section: Stress In University Studentsmentioning
confidence: 99%